The savvy investor's guide to pooled investments : mutual funds, ETFs, and more - Baker, H. Kent; Filbeck, Greg; Kiymaz, Halil (The savvy investor's guide, 2019)
Do you only have a relatively small amount of money to invest?Do you think this limitation give you only a few investment choices?Well, it doesn't.Investing experts H. Kent Baker, Greg Filbeck, and Halil Kiymaz offer an essential guide to one of the most common ways to invest: a pooled investment vehicle (PIV). A PIV is an investment fund that commingles the monies of many different investors to buy a portfolio that reflects a particular investment objective. By using PIVs, you gain a diversified portfolio, which once was only available to large investors.The Savvy Investor's Guide to Pooled Investments clearly explains the risks and advantages of investing in a PIV. This book introduces you to five PIVs - mutual funds, exchange-traded funds (ETFs), closed-end funds (CEFs), unit investment trusts (UITs), and real estate investment trusts (REITs) - with a unique Q&A format employed to delve into issues that investors want and need to know before choosing a PIV.If you have ever felt limited by your investment choices, Baker, Filbeck, and Kiymaz explain your options to creating an investment portfolio, which is an initial step to becoming a savvy investor.